Potential for Environmentally Friendly Business Practices Among Coffee Shop Business Owners in Thailand - Phoochinda, Wisakha; Patitas, Nicharnan (Local Administration Journal, 2024)
The study aims to analyze the potential and limitations of coffee shop owners in practicing environmentally friendly business and to propose guidelines for promoting such practices in the dimensions of production and services. Data were collected through surveys from 272 coffee shop owners in tourist areas in Thailand using accidental sampling and interviews with 15 coffee shop owners interested in environmentally friendly business practices. The data analysis includes descriptive statistics and qualitative data retrieved from interviews. The study's findings reveal that over half (59.56%) of the sample coffee shop owners have expectations for conducting business that supports environmentally friendly practices and demonstrates social and environmental responsibility. Most coffee shop owners repair equipment rather than buy new ones, with 81.62% doing so. Furthermore, the study found that most coffee shop owners are inclined to enhance their business’s environmental friendliness, starting with waste sorting at 79.60%. Coffee shop owners interested in conducting environmentally friendly businesses pay attention to sustainable development from upstream to downstream. This includes selecting chemical-free coffee beans and ensuring that the coffee production process does not harm the environment. They also focus on eco-friendly waste management. At the same time, they acknowledge common limitations due to the absence of supportive policies and initiatives from the government sector, such as the higher cost of environmentally friendly packaging compared to plastic packaging. Additionally, there is a lack of consumer awareness and promotion of sustainable consumption and limited support for producing organic coffee beans, all of which reflect a lack of commitment to societal responsibility.